Сонетний вірш Максима Рильського: структурно-композиційна і мовно-образна організація - Мойсієнко, А. (Культура слова, 2020)
Стаття присвячена опису динамічної системи та засобів її композиційно-образного творення в сонетних текстах Максима Рильського. Системна організація сонетного вірша Максима Рильського характеризується динамікою образного творення, що започатковується вже в першому катрені і, як правило, зберігає «лінію підйому» в другому катрені, щоб синтезою-розв’язкою відлунитися в заключних терцетах. У ряді текстів поета знаходить широке відбиття ідея внутрішньої конфліктності на стику двох катренів, проголошена свого часу у програмовому сонеті Івана Франка, хоч антитезний злам може відбуватися не лише на межі першого і другого катренів, започатковуватися протиставним сполучником, підсилювальною часткою (нерідко корелятом до них у першій частині виступає прислівник ще). Динамізації художньої структури сприяє текстова наскрізність повторюваних елементів на різних рівнях. The systematic organization of Maxym Rylskyi’s sonnet verse is characterized by the dynamics of figurative creation, which begins in the first quatrain and, as a rule, preserves the “rise line” in the second quatrain in order to echo the synthesis in the final thirds. Thus, in the sonnet «The ax trembles, the silver darkened» two lines ─ the trembling sedge, which rises high with the darkened silver leaf, and the benefit of the green shadow from it for the weary, aching human body ─ in the first quatrain they seem to run in parallel. However, already in the second quatrain, probably, from the same trembling ax the appeal of the lyrical hero to the heart sprouts (Tremble, develop and wormwood!). The synthesis-generalization initiated by the replica of the heart (internal monologue) continues the associative parallel of nature and man in the first third (On the branch of universal wood. You are only a particle, line one!) ─ both semantic lines marked at the beginning of the poem are now merged the only one. And finally the final concluding stanza ─ the assertion of this unity ─ earthly and high, when the only true dimension is the integrity of depth. Another structural organization is observed in the sonnet «In the warm days of grape harvest», where the first stanza of the exposition reveals to the reader a lyrical location, which in the second quatrain unfolds in the dialogue of lyrical characters and is continued in the castle stanza by a generalizing line, thus creating the overall compositional and artistic integrity of the poetic structure. In a number of texts the poet broadly reflects the idea of internal conflict at the junction of two quatrains, proclaimed at one time in the program sonnet of Ivan Franko, although the antithetical break can occur not only at the border of the first and second quatrains. the first part is an adverb yet). The whole sonnet is based on the features of such correlates. The textual permeability of repeating elements at different levels contributes to the dynamization of the artistic structure. In verse «Bring gifts to the gods! Transparent honey bear» repetition with an anaphoric conjunction and in each stanza (used more than ten times in the text) grows into a gradation of syntagms in the final stanzas.